Assessing land use and flood management impacts on ecosystem services in a river landscape (Upper Danube, Germany). (6th July 2020) - Stammel, Barbara; Fischer, Christine; Cyffka, Bernd; Albert, Christian; Damm, Christian; Dehnhardt, Alexandra; Fischer, Helmut; Foeckler, Francis; Gerstner, Lars; Hoffmann, Tim G.; Iwanowski, Janette; Kasperidus, Hans D.; et al.
Abstract: Rivers and floodplains provide many regulating, provisioning and cultural ecosystem services (ES) such as flood risk regulation, crop production or recreation. Intensive use of resources such as hydropower production, construction of detention basins and intensive agriculture substantially change ecosystems and may affect their capacity to provide ES. Legal frameworks such as the European Water Framework Directive, Bird and Habitats Directive and Floods Directive already address various uses and interests. However, management is still sectoral and often potential synergies or trade‐offs between sectors are not considered. The ES concept could support a joint and holistic evaluation of impacts and proactively suggest advantageous options. The river ecosystem service index (RESI) method evaluates the capacity of floodplains to provide ES by using a standardized five‐point scale for 1 km‐floodplain segments based on available spatial data. This scaling allows consistent scoring of all ES and their integration into a single index. The aim of this article is to assess ES impacts of different flood prevention scenarios on a 75 km section of the Danube river corridor in Germany. The RESI method was applied to evaluate scenario effects on 13 ES with the standardized five‐point scale. Synergies and trade‐offs were identified as well as ES bundles and dependencies on land use and connectivity. The ratio of actual and former floodplain has the strongest influence on the total ES provision: the higher the percentage and area of an active floodplain, the higher the sum of ES. The RESI method proved useful to support decision‐making in regional planning.